Complement deficiencies and dysregulation: pathophysiological consequences, modern analysis, and clinical management - Schröder-Braunstein, Jutta; Kirschfink, Michael (Molecular immunology, 2019)
Complement defects are associated with an enhanced risk of a broad spectrum of infectious as well as systemic or local inflammatory and thrombotic disorders. Inherited complement deficiencies have been described for virtually all complement components but can be mimicked by autoantibodies, interfering with the activity of specific complement components, convertases or regulators. While being rare, diseases related to complement deficiencies are often severe with a frequent but not exclusive manifestation during childhood. Whereas defects of early components of the classical pathway significantly increase the risk of autoimmune disorders, lack of components of the terminal pathway as well as of properdin are associated with an enhanced susceptibility to meningococcal infections. The impaired synthesis or function of C1 inhibitor results in the development of hereditary angioedema (HAE). Furthermore, complement dysregulation causes renal disorders such as atypical hemolytic uremic syndrome (aHUS) or C3 glomerulopathy (C3G) but also age-related macular degeneration (AMD). While paroxysmal nocturnal hemoglobinuria (PNH) results from the combined deficiency of the regulatory complement proteins CD55 and CD59, which is caused by somatic mutation of a common membrane anchor, isolated CD55 or CD59 deficiency is associated with the CHAPLE syndrome and polyneuropathy, respectively. Here, we provide an overview on clinical disorders related to complement deficiencies or dysregulation and describe diagnostic strategies required for their comprehensive molecular characterization - a prerequisite for informed decisions on the therapeutic management of these disorders.
Gesehen am 03.12.2019